Economical flow velocity in water distribution system - Selvakumar, Ariamalar; Orth, Hermann M.; Nguyen, Cong Thanh; Vigneswaran, Saravanamuthu; The Government of Norway (Bangkok : Asian Institute of Technology, 1984)
The purpose of this study is to find t he e conomicaltlow velocity in a water distribution system. The economical flow velocity in the pipe line depends on the roughness coefficient, energy cost , construction cost and present worth factor. A theoretical study was done to study the influence of above factors on economical flow velocity. When the system consists of a single pipe and a p ump the ec onomical flow velocity uoes b~ar a definite relation to tha diameter for a given set of costs. b ut in a distribution system , economical flow velocity depends on the hyd raulics of the networK a lso. Statistical analysis was done to study the distribution of economical f low velocity tor each diameter and Kolmogorov - Smirnov test was used to test the goodness of fit.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1984
Keywords: Water -- Distribution -- Mathematical models